Cannabinoid crystal polymorphism - Crist N. Filer (BMC, 2022)
Abstract Because cannabinoids are usually amorphous solids, the thought that some of them may also exist in distinctly different crystal polymorphic forms might at first seem unusual. However, this commentary provides compelling evidence and precedent for the likely existence of cannabinoid crystal polymorphism.